Single-port laparoscopic appendectomy using a needle-type grasping forceps for selective adult patients with acute uncomplicated appendicitis. Issue 1 (14th January 2022) - Chen, Yang; Liu, Yanjie; Guo, Shigang; Yuan, Jieqing; Li, Xiaojun
Abstract: Laparoscopic appendectomy has been performed by surgeons all over the world with the advantages of minimal injury. However, conventional multiple ports procedure still has room for improvement to further reduce surgical stress. We present a novel technique of single-port laparoscopic appendectomy using a needle-type grasping forceps (SLAN) for the treatment of uncomplicated appendicitis in adults, which produces just a 1 cm traumbilical incision. Fourteen adult patients underwent this technique without any complications. Many advantages were observed, including minimal surgical trauma, less pain, faster recovery and unobviousable scars. In conclusion, SLAN provides a new choice of minimal invasive procedure for surgeons to treat adult patients with acute uncomplicated appendicitis.